Transformasi Kebijakan Pidana Mati Dalam Undang-Undang No. 1 Tahun 2023 : Kajian Dari Perspektif Hukum Pidana - Guevara Julius Sabirin Putra; M. Farhan Hasan; Hafizhah Khairannisa; Muhammad Firlian Azizi (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The transformation of the old law into the new law has invited controversy from various public perspectives. The implementation of Law No. 1 of 2023 concerning the Criminal Code brings significant changes to the criminalization process in Indonesia, particularly in the regulation of the death penalty. While in the old Criminal Code, the death penalty was a principal punishment that could be directly imposed and implemented, the new regulation has transformed the policy, positioning the death penalty as a special punishment and being imposed as an alternative. This study aims to analyze the transformation of the death penalty policy in Law No. 1 of 2023 and examine it from a criminal law perspective. The research method used in this paper is normative legal research with a statutory and conceptual approach. The data for this research was obtained through a literature review of laws and regulations, legal literature, and expert opinions relevant to the death penalty policy.